2006
DOI: 10.1196/annals.1375.056
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones May Not Reduce Diabetes Incidence in Type 1 Diabetes

Abstract: Thiazolidinediones improve glycemic control by reducing insulin resistance. Some studies have demonstrated that troglitazone had a preventative effect on diabetes in NOD (non-obese diabetic) mice. One of the mechanisms proposed for the prevention of diabetes by thiazolidinediones is an effect on T-helper 1/T-helper 2 (Th1/Th2) balance. In this article, we attempted to clarify whether pioglitazone is also effective in preventing diabetes as compared to metformin, which has no immunological effect. Female NOD mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Our negative findings are supported by Shigihara et al (15) who showed no improvement in insulitis or cytokine profile in NOD mice treated with pioglitazone when compared to metformin. Similarly, Zdravkovic et al (16) failed to show improvement in HbA1c or a decrease in insulin requirements in obese adolescents with T1DM treated with pioglitazone.…”
Section: Discussionsupporting
confidence: 82%
“…Our negative findings are supported by Shigihara et al (15) who showed no improvement in insulitis or cytokine profile in NOD mice treated with pioglitazone when compared to metformin. Similarly, Zdravkovic et al (16) failed to show improvement in HbA1c or a decrease in insulin requirements in obese adolescents with T1DM treated with pioglitazone.…”
Section: Discussionsupporting
confidence: 82%